TRANSFORMASI KOPERASI MENUJU SOCIETY 5.0 UNTUK MENINGKATKAN PEREKONOMIAN INDONESIA - Ony Thoyib Hadi Wijaya; Kirana Salsabilla Citra Wijaya; Lely Maharani (Lembaga Pengembangan Kinerja Dosen, 2025)
Cooperatives, as one of the elements of Indonesia's economy, hold significant potential in enhancing community welfare. With technological advancements and shifting social dynamics toward the Society 5.0 era, cooperatives must undergo transformation to remain relevant. Society 5.0 emphasizes the integration of advanced technologies, such as the Internet of Things (IoT), artificial intelligence (AI), and big data, into social life to create a prosperous society. This article discusses the role of cooperatives as a cultural heritage, the challenges of digital transformation they face, and strategies to enhance Indonesia's economy through the application of technology in cooperatives during the Society 5.0 era. Based on literature reviews and analyses, cooperative transformation is deemed highly promising in supporting sustainable economic growth in Indonesia.